Rancang Bangun Aplikasi Warung Makan Sate Tancap Berbasis Web - Oswaldo Steven Carlo Wijaya; Prya Artha Widjaja (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
In the current era of technological development, many people are already using technology in their daily activities. Various sectors have also utilized technology to help their activities. Sate Tancap is a business in the Food and Beverage sector which is quite popular in the Tangerang area and has quite a lot of visitors and buyers every day. The stock or inventory recording system at Sate Tancap is experiencing difficulties and still uses records that are not yet computerized. This research aims to provide an application for admins and cashiers that can be used regarding the lack of a system for managing menus and inventory at the Sate Tancap food stall. This research uses the prototyping method, in this method the researcher analyzes stakeholder needs, then creates an initial system design, then this prototype is approved by stakeholders. So, researchers will carry out the next stage, namely creating a Sate Tancap application website. After that, it is implemented to users and related parties. The existence of a sales and inventory recording system application is useful for satay food stalls, especially for owners and cashiers so that sales activities are more effective and efficient.